Citra Pantai Bali dalam Antologi Puisi Impian Usai Karya Wayan Sunarta: Kajian Semiotik - Sinsya Dewi, Eirenne Pridari; Atmaja, Made Jiwa; Triadnyani, I G.A.A. Mas (Humanis; Vol 19 No 1 (2017))
Wayan Sunarta is a poet who productive in Bali. Corpulent Wayan Sunarta work who described the conditions the coast of Bali, one of his work describing the Bali’s beach is poetry. In an Anthology Impian Usai of Wayan Sunarta is much verse talk about the Bali’s beach. Verse selected by harmony with the theme research, the image of the Bali’s beach in poetry. The verse is, “Pesisir Jimbaran”, “Lovina”, “Kusamba”, “Pelabuhan Buleleng”, “Malam Pengantin di Pesisir Serangan”, “Catatan Reklamasi Pantai Serangan”, “Tanah Lot”, dan “Laut Bali”. This research using methods qualitative. The procedure the analysis used is as follows. First, collect and sort out about the Bali’s beach perspective. Secound, structural analysis rhymes in anthology Impian Usai of Wayan Sunarta. This research is only analyze the theme, meaning, diction, sound, allusion, and image. It is to support semiotic analysis. Third, analysis Bali’s beach image, use semiotic of Riffaterre theory. The analysis of anthology Impian Usai of Wayan Sunarta, can conclude that he is having two ways to described the condition of the Bali’s beach. First, using language figuratively metaphors and personification and use it to inflict impression romantic in described  the condition of Bali’s beach still wondersful and beautiful. Second, using meaning denotasi and language figuratively tropen and kakafoni to clarify criticisms of negative chage or the bad condition of Bali’s beach.
Keywords: poetry, the Bali’s beach, structure, semiotic